The Evaluation of Change in Psychosocial Risk With Caregivers of Children With Chronic Kidney Disease: A Short-term Longitudinal Mixed-Methods Study - Caroline C. Piotrowski; Kira Kudar; Julie Strong; Ashley Giesbrecht; Anne Kazak; Katerina Pappas; Gina Rempel; Aviva Goldberg (Canadian Journal of Kidney Health and Disease)
Background: The COVID-19 pandemic and its accompanying safeguards intensified many of the ongoing daily challenges faced by caregivers of young people with chronic kidney disease (CKD) both pre-transplant and post-transplant, and also created a variety of new and pressing concerns. Little is known about how these families managed this unexpected adversity in their lives. Objective: To evaluate change in psychosocial risk for families of young people with CKD during the COVID-19 pandemic health emergency from the perspective of caregivers. Design: A short-term longitudinal mixed-methods study with a convergent parallel design. Setting: Manitoba, Canada. Participants: Thirty-six caregivers of young people with CKD participated in a quantitative assessment prior to the pandemic; approximately half were transplant recipients. Thirteen were re-assessed during the pandemic (62% were caregivers of transplant recipients) using both qualitative and quantitative assessments. Methods: First, caregivers completed the Psychosocial Assessment Tool (PAT) prior to the pandemic. Second, caregivers were re-assessed using the PAT during the pandemic. They were also interviewed about their experiences. Changes in PAT scores over time were evaluated, including an investigation of whether psychosocial risk was related to transplant status. Interviews were coded using thematic analysis. In the interpretation stage, the qualitative findings were combined with the quantitative results to help explain the latter and reach a more fulsome understanding of caregivers’ experience. Results: Quantitatively, overall family psychosocial risk scores increased significantly during the pandemic health emergency, as did the domain of Caregiver Problems. Families of transplant recipients were found to be at significantly lower psychosocial risk pre-pandemic than families of transplant candidates. Coding identified Negative Pandemic Experiences, Positive Pandemic Experiences, and Coping Mechanisms. Mixed-methods analyses revealed several areas of convergence and divergence between the quantitative and qualitative findings. Limitations: Limitations included a small sample size that limited generalizability, single site data collection, and single caregiver report. Conclusions: Although overall family psychosocial risk increased during the pandemic, caregivers described several resilience processes and characteristics. A mixed-method approach provided a unique perspective that highlighted the value of integrating quantitative and qualitative findings. Results were discussed within the pediatric psychosocial preventive health model framework.